Maternal obesity and gestational weight gain. (October 2013) - O'Dwyer, V.; O'Toole, F.; Darcy, S.; Farah, N.; Kennelly, M. M.; Turner, M. J.
<x xml:space="preserve">Abstract</x> The aim of the study was to analyse gestational weight gain (GWG) according to body mass index (BMI) category and to explore the relationship between GWG and pregnancy complications. Women were recruited in the 1st trimester. Weight and height were measured and BMI calculated. Weight was measured at 38 weeks' gestation and GWG calculated. Clinical details were obtained prospectively. Of the 604 women recruited, 45.5% were primigravidas and 25.2% were obese. The overall mean GWG was 11.6 kg (SD 6.0). In obese women, the mean GWG was 10.4 kg (SD 7.5) compared with 12.6 kg (SD 5.7) in the normal BMI category (p < 0.001). Maternal obesity but not increased GWG was associated with an increased risk of induction of labour, caesarean section and pre-eclampsia. It was concluded that obese women were more likely to exceed GWG recommendations, despite lower GWG than non-obese women. Maternal obesity and not GWG increased the risk of pregnancy complications.